2010
DOI: 10.1051/0004-6361/201014665
|View full text |Cite
|
Sign up to set email alerts
|

HIFI observations of water in the atmosphere of comet C/2008 Q3 (Garradd)

Abstract: High-resolution far-infrared and sub-millimetre spectroscopy of water lines is an important tool to understand the physical and chemical properties of cometary atmospheres. We present observations of several rotational ortho-and para-water transitions in comet C/2008 Q3 (Garradd) performed with HIFI on Herschel. These observations have provided the first detection of the 2 12 −1 01 (1669 GHz) ortho and 1 11 −0 00 (1113 GHz) para transitions of water in a cometary spectrum. In addition, the ground-state transit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…This value best explains the brightness distribution of the 557 GHz line observed on 19 July (Szutowicz et al 2011 and in prep. ) and is consistent with values found in other comets Hartogh et al 2010). The model reproduces both the line intensity and the Doppler shift of the water line if we set Q H 2 O to 2.2 × 10 28 mol s −1 (Table 1).…”
Section: Modelling the Datasupporting
confidence: 87%
“…This value best explains the brightness distribution of the 557 GHz line observed on 19 July (Szutowicz et al 2011 and in prep. ) and is consistent with values found in other comets Hartogh et al 2010). The model reproduces both the line intensity and the Doppler shift of the water line if we set Q H 2 O to 2.2 × 10 28 mol s −1 (Table 1).…”
Section: Modelling the Datasupporting
confidence: 87%
“…To convert the observed line intensities into production rates (Table 1), we used an excitation model similar to that of Hartogh et al (2010, and Bockelée-Morvan et al (2012). Collisions with electrons use an electron density factor x ne = 0.2.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…At the nucleocentric distances observed a constant T kin = 40 K is assumed as previous work has shown this value to be a good approximation (Combi et al 1999). Observations of the 110 − 101 (557 GHz) water line in other comets have constrained xn e to 0.2 (Biver 1997;Biver et al 2007;Hartogh et al 2010). Previous observations of 1P/Halley have shown that xr e , a scaling factor that determines the boundary radius between collisional excitation predominantly caused by water-water and water-electron, is equal to unity (Balsiger 1990;Festou 1990).…”
Section: Radiative Transfer Modelmentioning
confidence: 99%
“…Adopted values for the other model parameters mentioned above are given in Table 1. Although this model makes some simplistic assumptions such as spherical symmetry of the outgassing, and in the irradiation and photochemistry of the water, the omission of vibrationally excited levels, and radiative transfer at infrared wavelengths a number of comet observations have been modeled with considerable success (Zakharov et al 2007;Hartogh et al 2010;Bockelée-Morvan et al 2012).…”
Section: Radiative Transfer Modelmentioning
confidence: 99%